THE INTELLECTUAL AND POLITICAL PROTAGONISM OF ANTONIETA DE BARROS - Gaya , Sidneya Magaly; Laffin, Maria Hermínia Lage Fernandes (Seven Editora, 2024)
This article, whose research is of a bibliographic nature, aims to present the contributions of the professor, director and deputy Antonieta de Barros in the formation of Santa Catarina society, from the perspective of the universalization of the right to education and, through the conquest of this right, access to the set of political rights of the population, analyzed based on the reflections of historians such as Michel de Certeau (2020) and Sidney Chalhoub (2010). In a context of frank consolidation of racist, classist and sexist structures, Antonieta was formed and affirmed herself as a great intellectual; columnist, director and contributor to periodicals; competent teacher and school principal; in addition to being respected by parliament, and reformulated relevant elements of the educational legislation of this state such as the change in the contents of women's professional schools, including the contents of instruction; the creation and regulation of the positions of School Group Director and School Inspector, and also that access to these positions occurred through competitive examinations; the creation of Teacher's Day, as a school holiday; in addition to fighting for the universalization of education and secondary education. Among the main conclusions, it argues that their protagonism and example contributed to the affirmation of the right to education, intellectual production and political participation of subalternized groups; in that context, women, the black population and the poor population, in Santa Catarina and in Brazil. DOI:https://doi.org/10.56238/sevened2024.027-008